The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1742-6723.2009.01209.x
|View full text |Cite
|
Sign up to set email alerts
|

Injuries significantly associated with thoracic spine fractures: A case–control study

Abstract: Cervical and lumbar spine injuries and rib fractures are significantly associated with T-spine fracture. The presence of these injuries should raise suspicion of concomitant T-spine injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…While the cervical vertebrae may be mobilised effectively in an awake supine patient, axial loading of thoracolumbar vertebrae through mobilisation is the most effective clinical manoeuvre to detect any pain from a stable fracture. Second, the presence of a cervical spine fracture has previously been shown to be associated with another spinal fracture,21 and this was confirmed in this study, necessitating imaging of the rest of the spine. The presence of any neurological deficit without pain is a further obvious variable, which necessitates imaging of the thoracolumbar vertebrae.…”
Section: Discussionsupporting
confidence: 77%
“…While the cervical vertebrae may be mobilised effectively in an awake supine patient, axial loading of thoracolumbar vertebrae through mobilisation is the most effective clinical manoeuvre to detect any pain from a stable fracture. Second, the presence of a cervical spine fracture has previously been shown to be associated with another spinal fracture,21 and this was confirmed in this study, necessitating imaging of the rest of the spine. The presence of any neurological deficit without pain is a further obvious variable, which necessitates imaging of the thoracolumbar vertebrae.…”
Section: Discussionsupporting
confidence: 77%
“…Associated injuries have been reported in around 60% of sternal fractures with a mortality rate of 25%–45%. [1519] The variation in the outcome rates across studies could be attributed to the patient age, time for diagnosis, the use of early CT scan imaging, type and severity of associated injuries, and the aggressive monitoring and management plan. [1420] In data extracted from the NTDB, Oyetunj et al .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported mortality rates in patients with sternal fractures ranging from 24% up to as much as 45% [5, 6]. This high mortality rate is due to associated thoracic, pulmonary, cardiac, and spinal injuries [7–11]. Other studies, however, have shown that only one-third of all patients with sternal fractures in fact also suffered from concomitant injuries [12].…”
Section: Introductionmentioning
confidence: 99%